Impact of nuclear energy and hydro electricity consumption in achieving environmental quality: Evidence from load capacity factor by quantile based non-linear approaches - Ozcan, Burcu; Depren, Serpil Kilic; Kartal, Mustafa Tevfik (Elsevier, 2024)
This research examines the impacts of nuclear energy consumption (NEC) and hydro electricity consumption (HEC) on environmental quality. In doing so, the study examines eight leading NEC countries representing 80% of total NEC by considering also impacts of HEC, using load capacity factor (LCF) as the most comprehensive environment indicator, and including data between 1995/Q4 and 2018/Q4 as the most recent available intersect data. Besides, quantile-on-quantile regression (QoQR) and Granger causalityin-quantiles (GCiQ) approaches are applied as base models and quantile regression (QR) is considered for robustness. The outcomes present that (i) NEC and HEC have a causal impact on the LCF; (ii) NEC has a generally increasing impact on the LCF at high levels of NEC in all countries except for France and the United States of America (USA); (iii) HEC has a generally decreasing impact on the LCF at high levels of NEC in all countries except for USA and Germany; (iv) the impacts of NEC and HEC on the LCF change according to countries and levels (i.e., quantiles) of NEC and HEC; (v) the QR approach validates the robustness of the outcomes. Hence, the outcomes highlight the significant impact of nuclear (hydro electricity) energy consumption in increasing (decreasing) environmental quality and the importance of quantile and country based analyses. Furthermore, based on the empirical outcomes, policy inferences are discussed. (c) 2023 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.
Keywords: LCF; Nuclear energy; Hydro electricity; Quantile approaches; Leading nuclear countries